STATICS OF ADSORPTION OF ANIONIC SURFACTANTS - Vira Sabadash; Oleh Konovalov; Anna Nowik-Zając (Environmental Problems, 2022)
The paper presents the results of the study of the statics of adsorption of surface-active substances from model solutions by activated carbonand zeolite. The results ofphotometric determination of the concentration of anionic surfactants before and after adsorption are presented. The results of adsorption capacity calculations are presented. The experimental results using the program (Langmuir 1.03) were numerically calculated. Sorption isotherms of sodium dodecyl sulfate indicate the mechanism of monomolecular physicaladsorption.A good convergence of experimental data andtheoretical calculations were established, the coefficient of determination R2>0.9, the value of the Chebyshev criterion 9·10-4 ... 2·10-4, and the root mean square deviation equal to 0were established.